Different Green Manures (Vicia villosa and Brassica juncea) Construct Different Fungal Structures, Including Plant-Growth-Promoting Effects, after Incorporation into the Soil - Waleed Asghar; Ryota Kataoka (Agronomy, 2022)
The application of green manure to soil improves soil health by increasing biological activity. However, little attention has been paid to the effects of different green manures on the microbiological community and soil function after incorporation. Here, it was found that the green manures of Vicia villosa (leguminous) and Brassica juncea (non-leguminous) have different fungal structures, despite the soil originally being the same. Moreover, some isolated strains showed plant-growth-promoting abilities. Three strains (H1: Penicillium spp., H2: Clonostachys spp., and H3: Trichoderma spp.) from leguminous-manure-incorporated soil and four strains (B1: Purpureocillium spp., B4: Taifanglania spp., B6: Trichoderma spp., and B10: Aspergillus spp.) from non-leguminous-manure-incorporated soil showed the potential for plant growth enhancement. Plant-growth-promoting traits revealed that four strains possessed phosphate solubilization and siderophore production, although none of them showed the ability to produce indole-3-acetic acid (IAA)-like compounds with/without tryptophan. In addition, higher extracellular enzyme activities—including endoglucanase and β-glucosidase activities—were also detected in the soil-incorporated green manures. In conclusion, this study suggests that different fungal structures appeared when different green manures were applied, which promoted plant growth. This indicates the potential benefits of promoting the incorporation of green manure into the soil.